Evolution of Social Behavior of Rural Society of Central Chernozem Region in XVII—XVIII Centuries - N. A. Zhirov; D. A. Lyapin (Научный диалог)
The issue of the evolution of the behavioral model of a rural society is raised on the example of three territories, the centers of which were large rural settlements of the Oryol (Navesnoye village), Lipetsk (Panikovets village) and Voronezh (Dankovo village) regions. The chronological framework of the work coincides with the first stage in the development of these settlements from their origin to the formation of Orthodox parishes with a developed settlement district, which historically had a close connection with the central settlement. Mass economic and other documentation of the 17th—18th centuries was chosen as the main source. The research methodology is associated with the use of the problem-chronological method within the local boundaries of three rural settlements, the historical-system method and modern approaches, including microdemographic ones. The social organization of the rural population of the local territories studied by the authors was dynamic, especially in the 17th century, when the military factor played a significant role in the history of the region. It is noted that during the 18th century the odnodvortsy gradually lose their economic initiative, and by the end of the century, landowners and their owning peasants began to play an important role in the development of territories. It is shown that single-dvor collectivism continued to exist at a later time, actually surviving until the beginning of the 20th century.